2012
DOI: 10.1007/s10278-012-9461-y
|View full text |Cite
|
Sign up to set email alerts
|

Interactive Visualization and Analysis of Multimodal Datasets for Surgical Applications

Abstract: Surgeons use information from multiple sources when making surgical decisions. These include volumetric datasets (such as CT, PET, MRI, and their variants), 2D datasets (such as endoscopic videos), and vector-valued datasets (such as computer simulations). Presenting all the information to the user in an effective manner is a challenging problem. In this paper, we present a visualization approach that displays the information from various sources in a single coherent view. The system allows the user to explore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Multimodal visualization techniques have been used to present all available information in an effective manner [10,11]. A series of studies related to image-guided medialization laryngoplasty were published by Kirmizibayrak et al [3], Jin et al [12], and Yim et al [13]. They established new programs specific to laryngoplasty that would be useful for such a procedure.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Multimodal visualization techniques have been used to present all available information in an effective manner [10,11]. A series of studies related to image-guided medialization laryngoplasty were published by Kirmizibayrak et al [3], Jin et al [12], and Yim et al [13]. They established new programs specific to laryngoplasty that would be useful for such a procedure.…”
Section: Discussionmentioning
confidence: 98%
“…One of the reasons for this high failure rate is that vocal folds are not visible to the surgeon during the procedure, leading to the need for educated guesses based on medical imaging (i.e. CT scans of the patient and laryngoscope videos) and the surgeon's domain knowledge [3]. Prof. Isshiki reported that the anterior commissure exists at the midpoint between the thyroid notch and the lower margin of the thyroid cartilage.…”
Section: Introductionmentioning
confidence: 99%
“…In [KYWH12], the authors present a system they call "magic lens visualization," providing overall context and specialized rendering at the focus of attention. A similar system is described in [DPLR10].…”
Section: Related Workmentioning
confidence: 99%
“…The first application of a magic lens in the medical domain for an improved dataset exploration was proposed by Viega et al [2]. Other researchers have further extended the focus+context paradigm to multiple volumetric lenses [16], various volume distortions-e.g., zooming [17][18][19], and different techniques for volume rendering [20][21][22].…”
Section: Introductionmentioning
confidence: 99%